STRATEGI PENINGKATAN PELAYANAN CATATAN SIPIL DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SEMARANG (Studi Kasus Kepemilikan Akta Kelahiran) - Dina Ismira Dewi; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Service improvement have goals to fix the service to be better. Public service is the focus of public administration in Indonesia and still become a problem that need attention and solution. When the child was born, every parents must to report their child to the institute so it will be noted and have a recognition as a citizen that called birth certificate. Birth certificate is the main identity that must be owned by every people so it will increasing the good administration that corresponding on Region’s Rule of Central Java Province No. 1/2017 that manage about population administration. The low of the ownership of birth certificate cause by the service that so difficult, so the writer need to do a research about service improvement. The method of the research using the qualitative descriptive approach, and the technique of the data collecting are interview, observation, and document research. When searching the best strategy in this research, the writer using SWOT analysis and Litmus Test. The result of the research are gotten six strategy issues that trait strategy. The strategy are increasing the coordination between employees so the need of the service of civil registration become higher and to increasing the service of civil registration with the stakeholder’s involvement. The recommendation that given are doing coordinating conference once in a month by all of the employees to make the employee’s thought become similar so that will not any chaotic between them and to increasing the cooperation with the hospital to give the updated data of the new born babies so the publishing of the birth certificate can be done soon.